Computer-Based System for the Design of Dynamic Vibration Absorbers - Fernández, Rafael; Rincón, Nohelis; Bukowitz, David (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A dynamic vibration absorber (DVA) is a second-order system, which is designed to attenuate the amplitude of vibrations in mechanical systems. It is designed as a secondary mass-spring system connected to the main system, tuning its natural frequency such that it coincides with the excitation frequency. This originates a force that opposes the excitation at all times. A computarized expert system capable to acquire and process data to calculate the DVA design parameters was developed. The resulting computer-based system was named DADVIB and it was executed in the Visual Basic programming environment and directed towards design the DVA for laboratory equipment. The signal of a velocity transducer is transmitted to a data acquisition card conected to a laptop; the frequency spectrum of the studied system was obtained by processing the data using the fast fourier transform algorithm. The parameters obtained with the software, effectively reduces the amplitude of vibrations up to 80% in rotating machinery tested in laboratory. DADVIB was developed looking forward to be used in the industry as a part of the rotating machineries mantainance programs